Understanding the Education System in Urban Communities (Indian Journal of Management and Language (IJML), 2024)
The individuals, belonging to all communities, categories and socio-economic backgrounds have recognized the meaning and significance of education. They have formed the viewpoint that education is the instrument, which not only imparts information in terms of academic concepts and lesson plans, but also in terms of ways that are necessary in emerging into moral and ethical human beings. The system of education within urban communities is well-developed. On the other hand, within rural communities, it is not in a well-developed state, hence, rural individuals migrate to urban communities in order to acquire education. The educators in educational institutions of all levels are having the primary goal of leading to effective growth and development of students. Furthermore, the teaching-learning methods, teaching-learning materials and instructional strategies are in a well-developed state. With advancements taking place, educators are making use of various types of modern, scientific and innovative methods and materials in the implementation of different types of tasks and activities within educational institutions of all levels. As a consequence, students are able to achieve educational goals and developments takes place of overall system of education. Therefore, it is understood on a comprehensive basis that system of education is well-developed within urban communities throughout the country. The main concepts that are taken into account in this research paper are, understanding importance of education system in urban communities, features of education within urban communities and advantages of acquiring education within urban communities.